Draft Annual Plan 1980-81 Tamil Nadu - Planning Commission (Planning Commission, 1979)
Statement Showing the Details Of Plan Schemes Under the Various Developmental Heads Abstract Showing the Details Of Plan Schemes Under the Various Developmental And Group Heads. Statement Showing the Details Of Plan Schemes Ahea Development
Finance Department Government of Tamil Nadu